Computers and the Wage Structure - Michael J. Handel (Levy Economics Institute of Bard College, 1999)
A leading explanation for the rapid growth in U.S. wage inequality in the last twenty years, consistent with both human capital and postindustrial theories, is that advanced technology has increased job skill requirements and reduced the demand for less skilled workers. Krueger's study (1993) showing a wage premium associated with using computers at work is one of the few that seems to provide direct supportive evidence. In this paper I use previously unexamined data to suggest that measured returns to computer use are upwardly biased. In addition, I find that most of the growth of inequality since 1979 occurred in the early 1980s, which is inconsistent with a primary role for computers. Finally, computer use at work had equalizing impacts on the gender wage gap and elsewhere in the wage distribution, as well as disequalizing impacts on the wage gaps between education groups. When the contribution of computer use to all components of the variance of wages is taken into account, computers seem to have had a net equalizing impact in the period Krueger studied. This casts significant doubt on this technology-based explanation of the growth in wage inequality.
Keywords: 330